Sex trafficking of adolescents and young adults in the United States. Issue 5 (October 2015) - Chaffee, Tonya; English, Abigail
<x xml:space="preserve">Abstract</x> Purpose of review Sex trafficking of adolescents and young adults is both a human rights violation and a public health problem, globally and in the United States. Healthcare providers, including obstetricians and gynecologists, interact with victims, often while they remain under their traffickers' control, but because of providers' lack of training in identification and response many victims go unrecognized and unaided. This review provides an overview of the definitions of sex trafficking and commercial sexual exploitation, contributing factors, health consequences, recruitment of victims, and identification and response by healthcare providers. Recent findings The literature on definitions and risk factors associated with sex trafficking is growing; however, literature on healthcare providers' role in addressing sex trafficking remains more limited. It is increasingly recognized that healthcare providers have an important role in victim identification and response and as advocates, collaborating with national, regional, and local agencies to increase awareness of sex trafficking as a public health problem and to address the needs of adolescent and young adult victims and survivors globally and in the United States. Summary As professionals who interact with adolescent and young adult victims of sex trafficking, healthcare providers have an important role: in collaboration with other professionals and agencies they can help to identify, respond to, extricate, protect, and advocate for victims and survivors.